The influence of social media on psychological well-being: Examination and outlook - Ordatii, Nataliia; Nykonenko, Olena; Barbashova, Iryna; Klymenko, Ivan; Hrytsaniuk, Vita; Никоненко, Олена Вікторівна (Malque Publishing, 2024)
The article is dedicated to assessing the impact of social networks on the mental health of the population. Social networks have gained global popularity and are integral to modern life. Currently, social networks are platforms for personal development, communication skills, and socialization, searching for like-minded individuals and new friends, maintaining personal blogs, distance learning, and work. This study aims to analyze the impact of social networks on the mental health of the population and assess the possible perspectives of this influence. Theoretical methods were used to achieve the set goal: studying, analyzing, and systematizing scientific literature data. Currently, approximately 60% of the world's population uses social networks, with approximately 40% of users using them not only for entertainment and relaxation but also for work and education, which determines their socioeconomic significance. According to statistics, the most popular social networks worldwide are Facebook, YouTube, WhatsApp, Instagram, WeChat, and TikTok. In addition, most social media users are registered in one or several of them. On the one hand, social networks can help people communicate regardless of distance, acquire new knowledge, meet like-minded individuals, exchange ideas, and increase social support. On the other hand, their excessive use is associated with the development of addiction, low self-esteem, levels of anxiety and depression, and deterioration of social and physical health. These problems are particularly acute with increasing time spent in the virtual world. Therefore, in recent years, there has been increased interest in studying the impact of social networks on the health of the population as a whole and persons in particular and in developing and implementing effective methods to prevent the negative aspects of their us. This is a promising direction for further research. © 2024 Malque Publishing. All rights reserved.
Keywords: communication; mental health; psychology; social media; social media impact; virtual reality; well-being